1999
DOI: 10.1037/0022-006x.67.6.1004
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation among college students in the United States.

Abstract: This study analyzed data from the 1995 National College Health Risk Behavior Survey (NCHRBS) to assess the prevalence of suicidal ideation among college students in the United States and to examine the association between suicidal ideation and substance use in this population. The NCHRBS used a mail questionnaire to assess health-risk behaviors in a nationally representative sample of undergraduate students. During the 12 months preceding the survey, 10% of the students had seriously considered attempting suic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
99
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 21 publications
6
99
4
Order By: Relevance
“…Due to drug use, young people have troubles in many areas and sever almost all ties with normal life. Our research results are consistent with those of previous studies (Brener et al, 1999;Borowsky et al, 2001;Field et al, 2001;Hallfors et al, 2004;Morris et al, 1995;Karamustafaoğlu et al, 2010;Remafedi et al, 1991;Shamsian, 2001;Wichstrom, 2000;Yalçın et al, 2009). Another significant finding is that Internet addiction significantly predicts the suicide risk of college students.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Due to drug use, young people have troubles in many areas and sever almost all ties with normal life. Our research results are consistent with those of previous studies (Brener et al, 1999;Borowsky et al, 2001;Field et al, 2001;Hallfors et al, 2004;Morris et al, 1995;Karamustafaoğlu et al, 2010;Remafedi et al, 1991;Shamsian, 2001;Wichstrom, 2000;Yalçın et al, 2009). Another significant finding is that Internet addiction significantly predicts the suicide risk of college students.…”
Section: Discussionsupporting
confidence: 83%
“…Alcohol abuse is also a predictor of suicide ideation in college students. A study by Brener, Hassan, and Barrios (1999) concludes that a relationship exists between drug use and suicide ideation in college students. Another study concludes that drug use in youth leads to increased suicidal ideation and behaviors (Felts, Chernier, & Barnes, 1992).…”
mentioning
confidence: 99%
“…We focused on indicators of belongingness because a sense of belongingness has been identified as a key factor in the adjustment of college students (see Lee & Davis, 2000, for a review). Brener et al (1999) found that among college students, being a member of a fraternity or sorority and living with a spouse or domestic partner reduced the odds of seriously considering attempting suicide. Living with a family member or partner might be a particularly salient protective factor for Asian American college students because family relationships and group orientation are important values in many collectivistic Asian cultures (Leong, Leach et al, 2007).…”
Section: Goals Of the Present Studymentioning
confidence: 99%
“…There is mounting evidence for the link between substance use and suicidal behavior (Westefeld et al, 2000). Specifically, tobacco and alcohol use have been found to be significant predictors of suicidal ideation among college students (Brener et al, 1999;Kisch et al, 2005). Substance use may foster suicidal behavior by enhancing impulsivity, reducing coping mechanisms, and impairing judgment (Brener et al, 1999;Westefeld et al, 2000) .…”
Section: Goals Of the Present Studymentioning
confidence: 99%
See 1 more Smart Citation